Effect of hydrogen sulphide on liver somatic index and Fulton's condition factor in Mystus nemurus - Hoque, M. T.; M. Yusoff, Fatimah; Law, A. T.; Syed, M. A. (The Fisheries Society of the British Isles, 1998)
The growth rate and liver somatic index were significantly (P<0.05) lower in Mystus nemurus exposed to hydrogen sulphide compared to controls. These differences increased with corresponding increases in hydrogen sulphide concentrations. No significant differences (P>0.05) in Fulton's condition factor were detected between the exposed fish and the controls. The results revealed that liver somatic index is a more sensitive indicator of hydrogen sulphide toxicity compared to Fulton's condition factor.